Environmental Safety of Transport and Technological Vehicles - Zakhid A. Godzhaev; Dmitriy V. Avramov; Nikolay V. Martynov; Boris N. Belousov; Viktor N. Dobromirov (Сельскохозяйственные машины и технологии)
Abstract. Intensified production, an increased fleet of vehicles with internal combustion engines, as well as increased operational mass of transport and technological vehicles continuously aggravate the environmental situation in the world every year. (Research purpose) To identify the main impacts made by the transport and technological vehicles on the environment and the problems associated with their disposal, as well as with the disposal of automobile and tractor tires. (Materials and methods) The authors have generalized the materials published in periodicals, as well as the results of bench, field and operational tests of the transport and technological vehicles. (Results and discussion) The authors have identified the problem of the destructive impact of the wheeled movers on the supporting road surface, the soil and the soil cover. Measurements have been taken under the contact area of several mover types and the values of the stress-strained state of the soil affected by these movers have been determined in the form of the distribution of normal stress diagrams. The authors have also studied the influence of the design features of transport and technological vehicles performing curvilinear motion on the track size and soil destruction and identified characteristic patterns of the track. Conclusion has been made that in winter the level of environmental pollution depends on the road surface condition and the use of chemical reagents for deicing. The authors have considered a possibility of using electrical-and-hydraulic technology for the disposal of transport and technological vehicles and stressed the need to form regulatory documents for the designing, operation and disposal of transport and technological vehicles, taking into account foreign experience in organizing the environmental management system, as well as environmental auditing and labeling, the procedure for assessing the environmental performance of production systems and products at all life cycle stages. (Conclusions) The paper presents the main impact factors of the transport and technological vehicles on the environment during their life cycle up to full disposal. The authors have proved the need for a safe and energy-saving electro-hydraulic technology for the disposal of electronic components and batteries of transport and technological vehicles based on selective destruction of plastic casings and the separation of pure noble, rare-earth and other metals and their alloys.